PERFORMANCE EVALUATION OF FOG COMPUTING WITH EDGE DEVICES IN MEDICAL IOT APPLICATION - Ranganathan, G. (IRO Journal on Sustainable Wireless Systems, 2019)
Monstrous development in the communication and its supporting software’s has made our day today necessities which were once in our dream into existence. One such is the internetwork of things. This IoTs which are the a merge of many different technologies is a dais for many tangible commodities that are enabled with embedded computing, information initiated by every such commodities are computed processed and were stored in a cloud in the days past proved to be very successful. But the problem aroused on the clamp down such as latency and heightened bandwidth consumption in which the latency was the very important criteria to be met for the time sensitized information’s that were to be processed so there arouse a need to bring down the time interval between the initiation and the response time of information. This becomes more indispensable in sectors like surveillance and medical field. So the paper proposes an intervening computation known as fogging between the cloud and IoT, in order to bring down the latency period in medical field and the performance evaluation are done on the grounds of , latency, bandwidth and energy consumption.